Application of MQL technique using TiO2 nanoparticles compared to MQL simultaneous to the grinding wheel cleaning jet - Lopes, Jose Claudio [UNESP]; Garcia, Mateus Vinicius [UNESP]; Volpato, Roberta Silveira [UNESP]; Mello, Hamilton Jose de [UNESP]; Fonteque Ribeiro, Fernando Sabino [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Rocha, Kleper de Oliveira [UNESP]; Neto, Luiz Dare [UNESP]; Aguiar, Paulo Roberto; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
The minimum quantity lubrication + nanofluid technique has proven to be feasible in machining processes, since it has shown potential for improvements through its lubri-refrigeration and heat removal characteristics, beyond increase the surface quality workpiece surface, while minimizing diametrical wheel wear. Also, the nanofluids are associated with decreasing the grinding power corroborates for process efficiency. In this way, this work evaluates the combination of the MQL + nanofluid (MQL + Nano) technique and compares its results with the cutting fluid abundant application (Flood) technique, traditional MQL and MQL associated with wheel cleaning jet (MQL + WCJ). Accordingly, the process output variables were analyzed: surface roughness (Ra), roundness error, diametral wheel wear, optical microscopy and microhardness from the workpiece ground surface, grinding power, specific energy grinding, acoustic emission, cutting fluid viscosity and transmission electron microscopy of the TiO2 nanoparticle used. The techniques applied in this work did not cause microstructural alteration in the workpieces, proving that the lubri-refrigeration methods are efficient. Even though the cutting fluid viscosity decreased by about 60% with the addition of TiO2 nanoparticles and the application of the MQL + Nano technique proved to be efficient in comparison to the traditional MQL, the MQL + WCJ application presented the best results among the alternative lubri-refrigeration techniques. Thereby, the MQL + WCJ corroborated to a better workpiece surface quality, while presented the lower diametrical wheel wear, surface roughness and roundness error values, contributing to the minimization of the industrial residues and cooperating with the environment and health of the worker.
Keywords: Grinding process; TiO2 nanofluid; Minimum quantity lubrification (MQL); wheel cleaning jet (WCJ); CBN wheel